2019
DOI: 10.1002/ps.5344
|View full text |Cite
|
Sign up to set email alerts
|

The importance of timing of heat events for predicting the dynamics of aphid pest populations

Abstract: BACKGROUND: Heatwaves are increasing in frequency and there is growing interest in their impact on pest organisms. Previous work indicates that effects depend on the timing of the stress event, whose impact needs to be characterized across the full set of developmental stages and exposure periods of an organism. Here, we undertake such a detailed assessment using heat stress (20-35 ∘ C diurnal cycle) across the nymph and adult stages of the English grain aphid, Sitobion avenae (Fabricius). RESULTS: Stress-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 90 publications
4
19
0
Order By: Relevance
“…Using an elegant experimental design with aphids, that varied the duration and relative frequency of 'normal' (13-28°C diurnal fluctuation) and 'hot' (20-35°C diurnal fluctuation) time periods, Ma et al (2018) demonstrated that the negative fitness consequences of a HW depend both on its duration (1-3 days) and on its temporal clustering. Responses to high temperature events may also vary with developmental timing and life stage (Zhang et al, 2015b;Banahene et al, 2018;Zhao et al, 2019). Our results for M. sexta similarly show that the consequences of HWs depend on timing within the larval stage, especially when there are multiple HWs.…”
Section: Discussionsupporting
confidence: 61%
“…Using an elegant experimental design with aphids, that varied the duration and relative frequency of 'normal' (13-28°C diurnal fluctuation) and 'hot' (20-35°C diurnal fluctuation) time periods, Ma et al (2018) demonstrated that the negative fitness consequences of a HW depend both on its duration (1-3 days) and on its temporal clustering. Responses to high temperature events may also vary with developmental timing and life stage (Zhang et al, 2015b;Banahene et al, 2018;Zhao et al, 2019). Our results for M. sexta similarly show that the consequences of HWs depend on timing within the larval stage, especially when there are multiple HWs.…”
Section: Discussionsupporting
confidence: 61%
“…Ectotherms do not maintain constant body temperature, as they apply behavioural, physiological, and cellular adjustments to maintain thermal homeostasis (Bicego et al ., 2007; Bodlah et al ., 2017; Green et al ., 2019). Extreme high temperature plays a major role in affecting ectotherms (Ma et al ., 2018; Cherif et al ., 2019; Zhao et al ., 2019). It influences the biological functions, geographical distribution, and species richness of insects, especially under climate change scenarios (Hu et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Even a brief exposure to extreme temperature could affect organism phenology (Semenov, 2009), species distribution (Overgaard et al ., 2014), population dynamics (Asin & Pons, 2001), community structure (Ma et al ., 2015), and sustained exposure to high temperatures, which may eventually lead to death (Chown & Terblanche, 2006; Hoffmann et al ., 2013). Therefore, determining the thermal tolerance is essential for understanding the effects of extreme heat events on a given population's fitness and dynamics under climate change scenarios (Terblanche & Chown, 2007; Zhao et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abiotic environment is vital to the development of most organisms, 1–3 and the earlier experience of this environment regulates development, but also partly induces it 4–6 . Previous studies have suggested that earlier experiences of environmental stressors can prompt plasticity responses 7 in fitness traits, including development, longevity and fecundity, 8,9 or induce changes in tolerance to other stressors 10,11 . Thus, exploring how adaptation to one environmental stressor impacts the tolerance and phenotypic plasticity to other stressors requires attention in a rapidly changing world.…”
Section: Introductionmentioning
confidence: 99%